Mental health in elite athletes: International Olympic Committee consensus statement - Reardon, C. L.; Hainline, B.; Aron, C. M.; Baron, D.; Baum, A. L.; Bindra, A.; Budgett, R.; Campriani, N.; Castaldelli-Maia, J. M.; Currie, A.; Derevensky, J. L.; Glick, I. D.; et al. (British Journal of Sports Medicine, 2019)
Mental health symptoms and disorders are common among elite athletes, may have sport related manifestations within this population and impair performance. Mental health cannot be separated from physical health, as evidenced by mental health symptoms and disorders increasing the risk of physical injury and delaying subsequent recovery. There are no evidence or consensus based guidelines for diagnosis and management of mental health symptoms and disorders in elite athletes. Diagnosis must differentiate character traits particular to elite athletes from psychosocial maladaptations. Management strategies should address all contributors to mental health symptoms and consider biopsychosocial factors relevant to athletes to maximise benefit and minimise harm. Management must involve both treatment of affected individual athletes and optimising environments in which all elite athletes train and compete. To advance a more standardised, evidence based approach to mental health symptoms and disorders in elite athletes, an International Olympic Committee Consensus Work Group critically evaluated the current state of science and provided recommendations.